SOLID-LIQUID FERMENTATION PROCESS FOR SOLID WASTE PALM OIL PROCESSING - Setyahadi., dkk, Siawa (BPPT)
The main elements contained in solid waste palm-called empty fruit bunches palm oil are 45-50% cellulose, 25-35% hemicellulose and lignin. Empty fruit bunches palm oil are used as compost feedstock in this study have a 56.49% of C-organic content, 0.34% of N-total, and 165.15 of C / N ratio.Solid waste oil palm is increasing in line with the needs of palm oil for household needs. While palm trees need a good fertilization in order to increase oil palm productivity. Traditionally, processing of empty fruit bunches palm oil to be composted,left on open land that will take a long time and vast land in accordance with its production capacity. By using solid-liquid fermentation is expected to occur with a rapid decomposition process with enzymatic hydrolysis and followed by higher temperature at 100 oC or 121oC. The result shows that, within 4 days of decomposition, a pH value between 6-8, the water content 70-80%, C content was decreased from 56% to 53-49%, increasing N-Total value start from 0, 34% to 0.9%, and decreased the C/N ratio from 165 to 58.keywords : empty fruit bunches palm oil, fermentation, compost, solid-liquid